Steam reforming of glycerol for hydrogen production: Modeling study - M. A. Soria (2016)
A phenomenological model that predicts the operation of a packed bed reactor for glycerol steam reforming (GSR), in terms of glycerol conversion and products generation (first time to our knowledge), especially H-2, was built and used to perform a parametric analysis (range of conditions: 748-848 K, water-to-glycerol feed ratios (WGFRs) of 3-12 and 1-5 atm). First, the model was validated in terms of glycerol conversion, products yields and selectivities, having been observed very good agreement. Regarding the parametric study, higher temperatures, WGFRs and pressures were found to be more beneficial in terms of glycerol conversion. Moreover, the H-2 yield and selectivity are enhanced when higher temperatures and lower WGFRs and pressures are employed. Still, the maximum amount of 4.93 mol of H-2/mole of glycerol fed to the reactor was observed at 848 K, WGFR of 9 and 2 atm. Copyright